Role of Autologous Blood Clot Seal in Reducing the Incidence of Pneumothorax Post CT-guided Lung Biopsy: A Randomized Control Trial - Shah, Aamir; Shera, Tahleel; Bhat, Mudasir; Maqsood, Shadab; Robbani, Irfan; Shah, Sanaullah; Wani, Inzimam (Journal of Clinical Interventional Radiology ISVIR, 2025)
The objective of this research study was to assess the safety and efficacy of employing autologous blood clot seal (ABCS) for lowering the occurrence of pneumothorax (PTX) after computed tomography (CT)-guided percutaneous lung biopsy.A prospective randomized controlled trial involving 100 patients, approved by our hospital's institutional ethics committee and registered in the Clinical Trial Registry of India (CTRI/2021/04/032746), was conducted. Adult patients undergoing percutaneous lung biopsy were included. Randomization of the patients was done, and they were allocated to two groups: Group A received biopsies with the ABCS application, while in Group B patients, biopsies were done without the use of ABCS. An 18G semi-automatic coaxial biopsy system was utilized. In Group A, ABCS was administered through the guiding needle upon removal of the biopsy gun. PTX occurrence was assessed immediately post-biopsy and at a 4-hour follow-up.Among the 50 patients in Group A, PTX developed immediately in 4 (8%) patients, with no change in frequency at the 4-hour follow-up. In contrast, among the 50 patients in Group B, PTX occurred immediately in 15 (30%) patients, and the frequency increased to 34% (17/50) at the 4-hour follow-up. The incidence of PTX was significantly lower in ABCS recipients both immediately and at the 4-hour follow-up (p-value = 0.009 and p-value = 0.003, respectively).ABCS is a simple, affordable, and safe intervention that lowers the incidence of PTX following CT-guided percutaneous lung biopsy. This method holds promise for improving patient outcomes in clinical practice.
Keywords: lung biopsy; autologous blood clot seal; pneumothorax; interventional radiologist